Exploring governance in two chains of academy schools: A comparative case study. (May 2014) - Salokangas, Maija; Chapman, Christopher
Although the number and size of academy chains in England is still increasing, the implications of these arrangements at a local level remain under-researched. This article reports findings from a comparative case study focusing on governance arrangements and sponsor involvement in two chains of academies. The findings suggest that the policy and practice of these multi-academy sponsors define the autonomy of the individual academies within the chains, so that the level of autonomy individual academies experience varies significantly between, as well as within, chains.